Visualizing metrics on areas of interest in software architecture diagrams - Byelas, H.; Telea, A. (2009 IEEE Pacific Visualization Symposium, 2009)
We present a new method for the combined visualization of software architecture diagrams, such as UML class diagrams or component diagrams, and software metrics defined on groups of diagram elements. Our method extends an existing rendering technique for the so-called areas of interest in system architecture diagrams to visualize several metrics, possibly having missing values, defined on overlapping areas of interest. For this, we use a solution that combines texturing, blending, and smooth scattered-data point interpolation. Our new method simplifies the task of visually correlating the distribution and outlier values of a multivariate metric dataset with a system's structure. We demonstrate the application of our method on component and class diagrams extracted from real-world systems.